Genome-Wide Characterization of the MADS-Box Gene Family in Radish (Raphanus sativus L.) and Assessment of Its Roles in Flowering and Floral Organogenesis - Li, Chao; Wang, Yan; Xu, Liang; Nie, Shanshan; Chen, Yinglong; Liang, Dongyi; Sun, Xiaochuan; Karanja, Benard K.; Luo, Xiaobo; Liu, Liwang (Frontiers in Plant Science, 2016)
The MADS-box gene family is an important transcription factor (TF) family that is involved in various aspects of plant growth and development, especially flowering time and floral organogenesis. Although it has been reported in many plant species, the systematic identification and characterization of MADS-box TF family is still limited in radish (Raphanus sativus L.). In the present study, a comprehensive analysis of MADS-box genes was performed, and a total of 144 MADS-box family members were identified from the whole radish genome. Meanwhile, a detailed list of MADS-box genes from other 28 plant species was also investigated. Through the phylogenetic analysis between radish and Arabidopsis thaliana, all the RsMADS genes were classified into two groups including 68 type I (31 Mα, 12 Mβ and 25Mγ) and 76 type II (70 MIKCC and 6 MIKC*). Among them, 41 (28.47%) RsMADS genes were located in nine linkage groups of radish from R1 to R9. Moreover, the homologous MADS-box gene pairs were identified among radish, A. thaliana, Chinese cabbage and rice. Additionally, the expression profiles of RsMADS genes were systematically investigated in different tissues and growth stages. Furthermore, quantitative real-time PCR analysis was employed to validate expression patterns of some crucial RsMADS genes. These results could provide a valuable resource to explore the potential functions of RsMADS genes in radish, and facilitate dissecting MADS-box gene-mediated molecular mechanisms underlying flowering and floral organogenesis in root vegetable crops.